2008
DOI: 10.1002/jor.20667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on vascularization during fracture repair

Abstract: Age affects fracture repair; however, the underlying mechanisms are not well understood. The goal of this study was to assess the effects that age has on vascularization during fracture healing. Tibial fractures were created in juvenile (4-week-old), middle-aged (6-month-old), and elderly (18-month-old) mice. The length density and surface density of blood vessels within fracture calluses were analyzed using stereology at 7 days after fracture. The expression of molecules that regulate vascular invasion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 38 publications
3
113
0
6
Order By: Relevance
“…Depletion and/or senescence of these cells may result in age-related tissue degeneration as well as decreased regenerative potential (20,21). Animal studies have shown significantly reduced bone regeneration capacity with aging (22,23). When compared with 4-week-old mice, middle-aged (6 months) and old mice (18 months) present less vascularized fracture callus and less bone regeneration (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Depletion and/or senescence of these cells may result in age-related tissue degeneration as well as decreased regenerative potential (20,21). Animal studies have shown significantly reduced bone regeneration capacity with aging (22,23). When compared with 4-week-old mice, middle-aged (6 months) and old mice (18 months) present less vascularized fracture callus and less bone regeneration (22).…”
Section: Discussionmentioning
confidence: 98%
“…Animal studies have shown significantly reduced bone regeneration capacity with aging (22,23). When compared with 4-week-old mice, middle-aged (6 months) and old mice (18 months) present less vascularized fracture callus and less bone regeneration (22). Up-regulation of the inflammatory response results in a lowlevel, long-lasting, systemic proinflammatory state, which underlies most age-associated diseases (24).…”
Section: Discussionmentioning
confidence: 98%
“…The length density (the length of blood vessels per unit volume of the reference space) and the surface density (the area of the outer surface of blood vessels per unit volume of the reference space) of the blood vessels within the fracture callus were analyzed using an Olympus CAST system, as described previously (Lu et al, 2008).…”
Section: Quantification Of Blood Vessels In Fracture Callusmentioning
confidence: 99%
“…Displacement is more common, and efficacies of some fracture repair techniques decrease relative to younger healthy patients. [3][4][5] Displaced distal radius fractures typically are repaired by closed reduction and casting or open reduction with internal plate fixation, although this treatment dichotomy can be inadequate for certain elderly patients. Re-displacement rates after closed reduction with splinting 6 approach 50%.…”
mentioning
confidence: 99%